Personality Traits and Self-Concept of Senior High School Students of a Catholic School in Antique - Alavata, Ma. Teresa E.; Maravilla, Ma. Wilma M. (Philippine Social Science Journal, 2020)
Distinct individuals show different emotional responses and behavior in a different environment. During transitions, students tend to adjust socially, emotionally, and academically. The persons’ dominant personality is a dynamic and structured set of characteristics that uniquely influence their environment, cognition, emotion, and behavior in different circumstances. Meanwhile, the word self- concept refers to the person’s interpretation or view as to himself. How someone can act depends on his sense of self, which he feels about himself, including power, weakness, and personality. Previous studies do not provide precise or conclusive proof of what personality trait is correlated with the concept of self. In addition, the personality characteristics and self- concept were typically studied by college students and addressed very limitedly in the sense of the senior high school, especially in an Antique Catholic School. Hence, the paper determines the personality traits of Senior High School students of a Catholic school in Antique during the School Year 2019-2020. Likewise, it assesses the level of their self- concept in the areas of self- esteem, self- image, and self- confidence relative to sex, parenting styles, involvement in school clubs/organizations, and birth order.